A FemmeNist ManiPedifesto. (April 2015) - Lerum, Kari
This is an autoethnography about the role of nail salons in relation to my own evolving feminist and femme consciousness. Through a story of desire, grief, isolation, and recuperation, I explore the ways that the development of my sexual and gender identities relies on women's intimacy within and across lines of commodification, race, class, and sexuality. In so doing, I attempt to reconcile my desire for high femme signifiers with working-class, anti-racist, and anti-colonialist solidarity, to articulate what I term a FemmeNist consciousness .